Convergent evolution of the annual life history syndrome from perennial ancestors - Hjertaas, Ane C.; Preston, Jill C.; Kainulainen, Kent; Humphreys, Aelys M.; Fjellheim, Siri (Frontiers in Plant Science, 2023)
Despite most angiosperms being perennial, once-flowering annuality has evolved multiple times independently across flowering plants and is thought to be one of the most labile life history trait syndromes. Much research has focused on discerning the adaptive forces driving the evolution of annual species, and in pinpointing traits that distinguish them from perennials. By contrast, little is known about how 'annual traits’ evolve, and whether the same traits and genes have evolved in parallel to affect independent origins of the annual syndrome. Here, we review what is known about the distribution of annuals in both phylogenetic and environmental space and assess the evidence for parallel evolution of annuality through similar physiological, developmental, and/or genetic mechanisms. We then use temperate grasses as a case study for modeling the evolution of annuality and suggest future directions for understanding annual-perennial transitions in other groups. Understanding how convergent traits evolve can help predict species responses to climate change and allows transfer of knowledge between model and agriculturally important species.